Participatory Research and Community Youth Development: VOICES in Sarasota County, Florida - Moya L. Alfonso; Karen Bogues; Meredith Russo; Kellie McCormack Brown (The University of Alabama, 2022)
This article reports a case study of community-based participatory action research conducted as a community youth development activity, demonstrating a trend toward engaging youth in youth development efforts. The project actively engaged middle school youth in their communities and offered an avenue through which they could contribute to matters of importance to them. Youth are presented as stakeholders in the research process. Concrete strategies for collaborating with youth are described and evaluated.